Current Forms of Capital Accumulation, the World of Labor and the Restructuring of Social Security in Brazil - Flávia Rebecca Fernandes Rocha; Epitácio Macário (Revista Katálysis)
This article demonstrates that the restructuring of rights to Brazilian social security benefits in a restrictive manner has deep connections with transformations in the world of labor and with the predominantly financial standard of capital accumulation. The objective is to discuss the mediations that operate between the worldwide financial movements of capital, the restructuring of the world of labor and counter-reforms in the social security system operated in the governments of President Fernando Henrique Cardoso and Luiz Inácio Lula da Silva. It defends that the obstacles to universalization of Brazilian social security cannot be resolved only within the scope of social protection policies, but must be related to the need for structural transformations in the Brazilian economy and  society.